Occupational Therapy Workforce in the United States: Forecasting Nationwide Shortages. Issue 9 (25th February 2015) - Lin, Vernon; Zhang, Xiaoming; Dixon, Pamela
Abstract: Background: As the baby boomer generation retires in growing numbers, the demand for occupational therapists specializing in geriatrics will be particularly strong. Currently, there is evidence that a workforce shortage exists in the field of occupational therapy (OT), and few studies have been published in this area to systematically examine the status of the OT workforce. Objective: To examine current and future OT job surplus/shortage trends within the United States. Design: Forecast models and grading methodology were developed to evaluate individual state OT job shortages from 2008 to 2030. Setting: Not applicable. Participants: Not applicable. Main Outcome Measurements: OT shortages, OT shortage ratios, and a report card were generated and compared among the 50 states in the United States. Results: On the basis of current trends, demand for OT services will outpace the supply of occupational therapists within the United States. Shortages are expected to increase for all 50 states through 2030. The number of states with a grade D or below will increase from 3 in 2010, to 18 in 2020, to 37 in 2030, respectively. By 2030, the 3 states with the greatest shortage ratios will be Arizona, Hawaii, and Utah. The 3 states with the largest OT shortages (the number of OT jobs) will be California, Florida, and Texas. States in the northeast are projected to have the smallest shortages whereas states in the south and west are projected to have the largest shortages. Conclusion: This study serves to provide health care professionals, policy makers, and stakeholders with a means of assessing current and future OT needs. Discussion of the issues surrounding OT shortages and ongoing assessment of supply and demand must ensue to mitigate the projected shortages.